A Facile Review On The Protection Of An Invention In Nigeria: Issues And Challenges - Paul Atagamen Aidonojie; Toyin Afolabi Majekodunmi; Oaihimire Idemudia Edetalehn; Omolola Janet Adeyemi-Balogun (Jurnal Hukum dan Peradilan, 2023)
The development of a nation relies on technological advancements and innovations. It is evident in the progress of countries such as the USA, China, and Russia, which are considered developed nations due to the contributions of their scientists and technicians. In contrast, Nigeria and many other African countries are categorized as developing nations primarily due to the slow pace of innovation. Despite this, the legal process of obtaining protection or a patent for inventions poses a significant challenge for scientists and technicians in Nigeria. In this regard, the study employs a hybrid research method to examine the issues and challenges related to the protection of inventions in Nigeria. A descriptive and analytical approach is used to analyze the data by distributing 253 questionnaires to respondents across various geopolitical zones in Nigeria. The findings reveal a limited number of scientists and technicians involved in technological innovation, and there are obstacles to obtaining patents or protection for inventions in Nigeria. These challenges often deter scientists and technicians from investing more effort in technological innovation. Therefore, it recommended and concluded that, for practical and improved technological innovation in Nigeria, the government should create an enabling environment and review the existing legal framework for obtaining patents over inventions.